CPW-fed flower-shaped patch antenna for broadband applications - Patre S.R.; Singh S.P. (My University, 2025)
In this article, the simulation and experimental studies on a novel compact and broadband coplanar waveguide (CPW)-fed flower-shaped microstrip patch antenna are reported. The proposed flower-shaped patch is a modified version of circular patch. Although the proposed antenna has largest radius (= 12.5 mm) equal to the radius of a circular patch, it provides much wider impedance bandwidth and lower first resonant frequency as compared with the CPW-fed circular patch antenna. The flower-shaped patch itself is capable of providing good impedance match with the CPW feed without any modification of feed line and ground plane. The simulated input and radiation characteristics of the proposed antenna are compared with the corresponding experimental characteristics over the operating frequency range. The simulated and experimental input VSWR bandwidth (VSWR ≤ 2) of antenna are found to be 4.59:1 (2.2-10.1 GHz) and 4.81:1 (2.2-10.6 GHz), respectively. The antenna provides bidirectional and omnidirectional patterns in E- and H-planes, respectively, along with average gain value of 3.89 dB and good radiation efficiency (more than 75%) over whole operating frequency range. Time domain behavior of the antenna is also analyzed along with system fidelity factor and group delay. © 2015 Wiley Periodicals, Inc.